Galectin-3 in Cardiovascular Health: A Narrative Review Based on Life’s Essential 8 and Life’s Simple 7 Frameworks - Adrian Martuszewski; Patrycja Paluszkiewicz; Rafał Poręba; Paweł Gać (Current Issues in Molecular Biology)
Gal-3, also known as galectin-3, a lectin that binds β-galactosides, has gained attention as a novel biomarker and pathophysiological mediator in cardiovascular disease, where it contributes to inflammation, fibrosis, metabolic dysregulation and cardiac remodeling. This narrative review, developed following SANRA (Scale for the Assessment of Narrative Review Articles) guidelines, aims to integrate current clinical and experimental findings on gal-3 into the American Heart Association Life’s Simple 7 (LS7) and Life’s Essential 8 (LE8). By thematically organizing our review across modifiable domains of cardiovascular health, including glucose regulation, lipid metabolism, physical activity, blood pressure, diet, sleep, tobacco use, and body weight (BMI, body mass index), we highlight the role of gal-3 in linking environmental, behavioral and molecular risk factors to cardiometabolic outcomes. Particular attention is given to the oxidative stress, inflammatory–fibrotic axis, and immune activation as mechanistic pathways underlying gal-3-associated cardiovascular damage. We also discuss its relevance to public health and prevention, considering gal-3’s potential for early risk stratification, monitoring lifestyle interventions and personalized prevention strategies. This review bridges molecular mechanisms with clinical and public health relevance, particularly in the context of environmental and lifestyle-related cardiovascular risk.